Cancer patients as frequent attenders in emergency departments: A national cohort study - Ting Hway Wong; Zheng Yi Lau; Whee Sze Ong; Kelvin Bryan Tan; Yu Jie Wong; Mohamad Farid; Melissa Ching Ching Teo; Alethea Chung Pheng Yee; Hai V. Nguyen; Marcus Eng Hock Ong; N. Gopalakrishna Iyer (Cancer Medicine)
Abstract Background Cancer patients contribute significantly to emergency department (ED) utilization. The objective of this study was to identify factors associated with patients becoming ED frequent attenders (FA) after a cancer‐related hospitalization. Methods A retrospective cohort study was conducted using national administrative, billing, and death records of Singapore residents discharged alive from Singapore public hospitals from January 2012 to December 2015, with a primary discharge diagnosis of cancer. Patients with four or more ED visits within any 12‐month period after discharge from their index hospitalization were classified as FA. Time to FA distribution was estimated using the Kaplan‐Meier method, and factors associated with risk of FA were identified using multivariate Cox regression analyses. Results Records for 47 235 patients were analyzed, of whom 2980 patients were FA within the study period. Age (<17 years, hazard ratio [HR] 2.92, 95% CI 2.28‐3.74; 75‐84 years, HR 1.29, 95% CI 1.16‐1.45; and ≥85 years, HR 1.71, 95% CI 1.45‐2.02, relative to age 55‐64), male gender (HR 1.26, 95% CI 1.16‐1.37), Charlson comorbidity index (HR 1.21, 95% CI 1.19‐1.23), and socioeconomic factors (Medifund use, HR 1.40, 95% CI 1.23‐1.59; housing subsidy type, HR 2.12, 95% CI 1.77‐2.54) were associated with increased risk of FA. Primary malignancies associated with FA included brain and spine (HR 2.51, 95% CI 1.67‐3.75), head and neck cancers (tongue, HR 2.05, 95% CI 1.27‐3.31; hypopharynx, HR 2.72, 95% CI 1.56‐4.74), lung (trachea and lung, HR 1.57, 95% CI 1.13‐2.18; pleural, HR 3.69, 95% CI 2.12‐6.34), upper gastrointestinal (stomach, HR 1.93, 95% CI 1.26‐2.74; esophagus, HR 4.13, 95% CI 2.78‐6.13), hepato‐pancreato‐biliary (liver, HR 1.42, 95% CI 1.01‐2.00, pancreas, HR 2.48, 95% CI 1.72‐3.59), and certain hematological malignancies (diffuse non‐Hodgkin's lymphoma, HR1.59, 95% CI 1.08‐2.33, lymphoid leukemia, HR 1.86, 95% CI 1.21‐2.86). Brain (HR 1.69, 95% CI 1.27‐2.26), lung (HR 1.31, 95% CI 1.01‐1.71), liver (HR 1.46, 95% CI 1.14‐1.89), and bone (HR 1.35, 95% CI 1.04‐1.76) metastases were also associated with FA. Conclusion There are cancer‐specific factors contributing to ED frequent attendance. Additional resources should be allocated to support high‐risk groups and prevent unnecessary ED use.